Sistem Pelatihan Jarak Jauh (PJJ) Balai Diklat Keagamaan Medan Berbasis Web Menggunakan Learning Management System (LMS) Moodle - Muhammad Fajar Zain (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
The training process held by the Medan Religious Education and Training Center (BDK) is still carried out using the classical method, it means that training process can be established on the condition that there is a meeting between committee, participants and lecturers in a class. The Covid-19 pandemic, which has not ended until now, means that using classical training cannot be done optimally. Therefore, distance training method (E-Learning) was developed as a solution to the that problem. To support the successful implementation of the training, a web-based system for distance training process is needed as a media between committee, participants and lecturers. The Web-based system using Learning Management System (LMS) Moodle version 3.10.7. The method of system design uses the System Development Life Cycle (SDLC) approach with the Waterfall method. It is recommended that a Distance Training System be provided with technical instructions for using the system.